(untitled) (Journal of the Bangladesh Agricultural University, 2026)
Climate change has increased the frequency and intensity of cyclones in Bangladesh’s coastal regions, significantly affecting agricultural productivity. Therefore, implementing farm-level adaptation strategies against cyclones is essential to sustain and enhance crop productivity in these vulnerable areas. This study addresses this gap by examining farm-level vulnerabilities, cropping system impacts, and indigenous adaptation strategies across two highly cyclone-vulnerable districts (Patuakhali and Jhalokathi) in the south-central coastal region of Bangladesh. Utilizing a robust multi-stage random sampling design, primary empirical data were collected from 200 strictly screened smallholder households and systematically integrated with multi-decadal secondary meteorological data. The empirical results reveal severe, compounding seasonal disruptions, with Transplanted Aman (T. Aman) rice suffering the highest vulnerability, accounting for over 50% of aggregate cyclonic crop damage. Cyclonic storm surges trigger extensive economic losses averaging BDT 20,000-35,000 (163-285 USD) per household, primarily driven by secondary hazards such as rapid salinity intrusion, soil erosion, and prolonged waterlogging. While 79% to 80% of farmers perceive an accelerating frequency of cyclonic events, their current reactive adaptations (e.g., shifting planting timelines) are heavily constrained by indigenous knowledge and lack structural or technological scaling. Furthermore, 57% to 61% of smallholders identify the lack of institutional support and dedicated financial subsidies as the primary barriers to sustainable adaptation. These findings underscore an urgent need to transition from autonomous, experience-based coping mechanisms toward structural, zone-specific adaptation policies. This research provides a scalable framework for integrating empirical farmer perceptions with scientific weather analytics to engineer climate-resilient coastal agricultural systems globally. J Bangladesh Agril Univ 24(2): 118–128, 2026